Analisis Financial Distress Pada Perusahaan yang Terkena Isu Boikot Menggunakan Model Grover - Rifki Iswana, Ichsan; Anggraini Aripratiwi, Ratna (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
The issuance of MUI Fatwa No.83 of 2023 decided that supporting the struggle for Palestinian independence against Israeli aggression is obligatory. This support includes zakat, infaq and alms for the benefit of the Palestinian people's struggle. And a recommendation was issued as well as an appeal to Muslims to avoid transactions and use of products affiliated with Israel. Boycott actions that impact company finances can cause companies to experience financial distress. Therefore, researchers will conduct a financial distress analysis on 3 companies affected by the boycott issue. By using secondary data where financial reports and annual reports published by the IDX are the material in this research and by using the Grover Model as a tool for prediction. The results of the financial distress analysis using the Grover model as a predictor were 3 companies that were deemed capable of surviving enough to not experience financial distress, namely PT Unilever Indonesia Tbk, PT Mitra Adiperkasa Tbk, and PT MAP Boga Adiperkasa Tbk., then there were 2 companies identified as experiencing financial distress in 2023, namely PT Sarimelati Kencana Tbk and PT Fast Food Indonesia Tbk. With these results, the hypothesis is declared completely rejected. This is reflected in the results of the Grover model analysis, where the two companies experiencing financial distress have experienced poor financial performance due to Covid-19.